2017
DOI: 10.1097/sla.0000000000002230
|View full text |Cite
|
Sign up to set email alerts
|

30-day Readmission After Pancreatic Resection

Abstract: Readmission after pancreatic resection is common and can largely be attributed to infectious complications and inability to maintain adequate hydration and nutrition. Focus on outpatient resources and follow-up to address these issues will prove valuable in reducing readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…There has also been little progress in preventing common and often costly post-PD complications. Meta-analysis and multi-institutional studies demonstrate that infectious complications, failure to thrive, DGE, and complication severity drive readmission 13 , 14 , 17 , 18 and therefore represent cost saving opportunities. 5 , 8 Despite this knowledge, there has been little progress in the preventing or improving treatment of the most common post-PD complications.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been little progress in preventing common and often costly post-PD complications. Meta-analysis and multi-institutional studies demonstrate that infectious complications, failure to thrive, DGE, and complication severity drive readmission 13 , 14 , 17 , 18 and therefore represent cost saving opportunities. 5 , 8 Despite this knowledge, there has been little progress in the preventing or improving treatment of the most common post-PD complications.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical synthesis is expected to solve this issue 40. However, pooling multivariate data can be misleading as adjusted variables and the final model will be diverse between studies 41. Besides, prognostic factors will be determined based on statistically significant results and the consistency of findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-level risk factors included hospital bed count, hospital cancer discharge volume, hospital pancreatic cancer discharge volume, hospital pancreatic surgery volume, hospital location, and hospital ownership (e.g., nonprofit). The effect of hospital size on readmission was inconsistent in the existing literature; thus, we aimed to understand whether hospital size has an impact on readmission by using four different measures representing hospital size [5]. Hospital bed count was calculated within NRD data.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated this topic, but variations existed in approach. Studies differed in the time frame used for readmission, the definition of risk factors, surgery types, and the data source [5]. Not surprisingly, the results of these studies were also different, with reported readmission rates ranging from 6% to 59% [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation